Unlearn your pain : the science of recovering from chronic pain, fatigue, anxiety, and depression - Schubiner, Howard (Viking, 2026)
"Based on the life-saving research and more than twenty years of clinical trials and practice, Unlearn Your Pain is a ground-breaking guide to reversing chronic pain and overcoming anxiety and depression. AN OPEN FIELD PUBLICATION FROM MARIA SHRIVER Migraines, headaches, back pain, fibromyalgia, irritable bowel syndrome, chronic fatigue, and a host of other chronic illnesses have crippled the modern American population. For the past twenty years, Dr. Howard Schubiner has been conducting clinical trials and authoring more than 100 scientific papers and lectures to get to the root cause of how to reverse these insidious illnesses. In Unlearn Your Pain, he shares in inspiring and step-by-step detail the program steeped in the latest neuroplasticity research that has proven most effective in treating chronic pain, anxiety, and depression. The source of much of chronic pain is neurological and the book details a revolutionary program to better health that has saved thousands from a lifetime of misery and depression. Using the latest practices in the mind-body connection, all confirmed by clinical trials and studies, Dr. Schubiner leads readers to a new understanding of how the mind affects our pain, physical and emotional, and how we can gain control over our bodies and minds to live a healthier and better life"-- Provided by publisher.